SAT0472 Ulnar occlusion is a marker of global vascular damage in systemic sclerosis: results from a monocentric prospective study of 99 patients. (12th June 2018) - Yelnik, C.M.; Elodie, D.; Lamotte, C.; Sobanski, V.; Morell-Dubois, S.; Maillard, H.; Lambert, M.; Hatron, P.-Y.; Launay, D.; Hachulla, E.
Abstract : Background: Macrovascular damages of systemic sclerosis (SSc) were poorly investigated, and the link between macrovasculopathy and microvasculopathy of SSc, cardiovascular disease, and mortality remain unclear. Objectives: To evaluate if macrovascular damage in SSc predicts the occurrence of new digital ulcers (DU), cardiovascular events and mortality, and to further assess the relationship between micro and macrovascular damages in SSc. Methods: All consecutive SSc patients followed in our SSc National Reference Centre, who underwent an arterial doppler ultrasonography (aDUS) of the upper limbs, were included and prospectively followed up until October 2017. Inclusion criteria were: 1) adults; 2) a diagnosis of SSc according to 2013 ACR/EULAR criteria; 3) aDUS performed in our vascular exploration department. Results: Ninety-nine SSc patients were included. Median follow-up duration was 35 (IQR, 21 to 39) months. Macrovascular damages mainly affected ulnar arteries, with ulnar artery occlusion (UAO) in 28 (28.3%) patients (bilateral 60.7%). New DU occurred in 26 (27.1%) patients, new cardiovascular event in 10 (10.4%) patients, and 11 patients died during the study period. Interestingly, UAO was not associated with traditional cardiovascular risk factors (except dyslipidemia) nor with history of cardiovascular diseases, and was not predictive of new cardiovascular events. Conversely, UAO was associated with makers of microvascular damages, such as late nailfold capillaroscopy pattern (33.3% vs 6.8%; OR=6.88, 95% CI=1.76 to 26.82; p=0.03) and was predictive of new ischaemic DU (44.5% vs 24.8%; HR=2.23, 95%CI=1.02 to 4.86; p=0.037), pleading for a SSc specific vasculopathy. Conclusions: Our study confirms that macrovascular damages are frequent in SSc patients and mainly affect ulnar arteries. Interestingly, UAO was associated with severe microvasculopathy, but not with markers of cardiovascular diseases. Disclosure of Interest: None declared